EDUKASI PENGUATAN SUMBER DAYA KADER POSYANDU DI DESA LOKUS STUNTING KABUPATEN LABUHAN BATU, SUMATERA UTARA - Yeffi Masnarivan; Denas Symond; Erwinda Erwinda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Stunting is a condition of failure to thrive in children under five as a result of chronic malnutrition, so that children are shorter for their age. Malnutrition occurs when the baby is in the womb and in the early stages of life after birth, but is only seen after the child is 2 years old. Stunting has an impact on intelligence levels, vulnerability to disease and reduces productivity and results in hampering economic growth and increasing poverty and inequality in the future. For this reason, it is necessary to increase the capacity of cadres in community empowerment for stunting prevention. This activity aims to provide orientation to cadres and provide strengthening of HR (Human Resources) for an integrated service center in Lokus Stunting Village. The method of activity is carried out through education to cadres in the context of strengthening posyandu in an effort to prevent stunting. The orientation was held for one day in Labuhan Batu Regency as one of the stunting locus districts with 65 participants. The activity begins with an introduction by the team. The next activity is education with orientation materials consisting of (1) health efforts at posyandu for prevention of stunting, (2) interpersonal communication in health efforts at posyandu on adaptation of new habits, (3) implementation of health efforts in posyandu on adaptation of new habits, ( 4) making a follow-up plan after the cadre orientation activity. From the results of the activity, it was found that there was an increase in participants' knowledge after the orientation of cadres and strengthening of posyandu human resources (post-test) compared to before the activity (pre-test).